High-mass star formation in Orion B triggered by cloud–cloud collision: Merging molecular clouds in NGC 2024. (17th June 2020) - Enokiya, Rei; Ohama, Akio; Yamada, Rin; Sano, Hidetoshi; Fujita, Shinji; Hayashi, Katsuhiro; Tsutsumi, Daichi; Torii, Kazufumi; Nishimura, Atsushi; Konishi, Ryotaro; Yamamoto, Hiroaki; Tachihara, Kengo; et al.
Abstract: We performed new comprehensive 13 CO( J = 2–1) observations toward NGC 2024, the most active star-forming region in Orion B, with an angular resolution of ∼100″ obtained with Nanten2. We found that the associated cloud consists of two independent velocity components. The components are physically connected to the H ii region as evidenced by their close correlation with the dark lanes and the emission nebulosity. The two components show complementary distribution with a displacement of ∼0.6 pc. Such complementary distribution is typical to colliding clouds discovered in regions of high-mass star formation. We hypothesize that a cloud–cloud collision between the two components triggered the formation of the late O-type stars and early B stars localized within 0.3 pc of the cloud peak. The duration time of the collision is estimated to be 0.3 million years from a ratio of the displacement and the relative velocity ∼3 km s −1 corrected for probable projection. The high column density of the colliding cloud ∼10 23  cm −2 is similar to those in the other high-mass star clusters in RCW 38, Westerlund 2, NGC 3603, and M 42, which are likely formed under trigger by cloud–cloud collision. The present results provide an additional piece of evidence favorable to high-mass star formation by a major cloud–cloud collision in Orion.